Clothing, Embodied Identity, and Dementia: Maintaining the Self through Dress - Buse, Christina; Twigg, Julia (Age, Culture, Humanities: An Interdisciplinary Journal, 2015)
Clothes are central to how we perform our identities. In this article, we show how these processes continue to operate in the lives of people with dementia, exploring the ways in which dress offers a means of maintaining continuity of self at a material, embodied level. The article thus contributes to the wider cultural turn in aging studies, showing how material objects are signifcant in meaning-making, even for this mentally frail group. The article draws on the Economic and Social Research Council (ESRC)-funded study “Dementia and Dress,” which examined the implications of clothing for people with dementia, carers, and care workers, using ethnographic and qualitative methods. It showed, despite assumptions to the contrary, that dress remained signifcant for people with dementia, continuing to underwrite identity at both the individual level of a personal aesthetic and the social level of structural categories, such as class, gender, and generation. The article explores how identity is performed through dress in social interaction, and the tensions that can arise between narrative and embodied enactment and around the “curation” of identity. Dress provides a lens for understanding the lives of people with dementia, while at the same time, focusing on dementia expands discussions of fashion, consumption, and cultural meanings of aging.